Screening conditions and constructs for attempted genetic transformation of C. elegans by Agrobacterium - Eleanor C. Warren; André E. X. Brown; Karen S. Sarkisyan (PLoS ONE, 2025)
Manipulating gene expression within a model organism is important for reverse genetic experimentation, and while techniques to generate transgenic C. elegans are available, they are optimised for creating individual lines. The ability to create libraries of genetically modified animals using C. elegans as a model would make new types of experiments possible and would speed up studies of animal physiology. Here, we describe a range of constructs designed to establish a high-throughput method of C. elegans transformation mediated by gene transfer from Agrobacterium. We demonstrate that C. elegans are able to survive on Agrobacterium as a sole food source, and screen conditions for Agrobacterium-mediated transformation in this organism. While we do not achieve routine gene transfer from Agrobacterium to C. elegans, we suggest that this technique has potential following further optimization. The success of the approach would enable rapid and high-throughput transformation of C. elegans, providing an improvement on currently available methods . Here we provide details of optimization conditions tested, and a useful resource of T-binary constructs for use by the scientific community.